A Classification of Product Service System Concept in the Environmental Aspect to Create the Strategy of the Design of PSS - Ornwiriya Namsawat; Yanin Rugwongwan (My University, 2017)
Product Service System (PSS) is one of the procedures used to control the environmental problems arising from products and demand for product consumption. The method is aimed at creating a business system that sells products and boosts services for the maximum benefit of consumers. However, the PSS concept has many dimensions in the context of economy, society, and environment which are prioritized differently. This research is aimed at studying the literature review of PSS based on the environmental significance. The objective of this research is to analyze and classify the PSS factors in the environmental dimension and explain the factors affecting the creation of PSS strategy.Keywords: Product Service System; Design for Environment; Product Service Design Strategies; Sustainable Consumption.ISSN: 2398-4287© 2017. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.
Keywords: Product-service system; Consumption; Service and Product Innovation